Conversational avoidance during existential interviews with patients with progressive illness. Issue 9 (20th October 2020) - Martin, Vanessa; Sarker, Tasmie; Slusarek, Emily; McCarthy, Mary A.; Granton, John; Tan, Adrienne; Lo, Christopher
ABSTRACT: We examined patterns of avoidance when existential emotional topics were raised during conversations with patients with pulmonary arterial hypertension (PAH), an incurable life-limiting disease. 30 adult outpatients with PAH were recruited for a 20 to 60-minute interview about their illness experience. Qualitative content analysis was used to identify avoidance strategies that patients employed. Participants averaged 58 years in age (SD = 18), 77% were female, and mean length of illness was 6.3 years (SD = 5.3). We found four avoidance strategies: (1) Reversal, when individuals would begin discussing a negative concern and then backtrack to more positive sentiments; (2) Diversion for when patients would sidetrack the conversation to a different and less uncomfortable topic; (3) Diminishment for when a concern is raised and then made to seem unimportant; and (4) Obstruction, when patients refuse to discuss a concern further. Exploration of existential concerns can elicit distress but may be necessary to promote adaptation to progressive illness and to the foreseeable challenges that may affect the sense of life meaning and value. By recognizing when existential concerns may be present but not adequately discussed, clinicians may be better able to assist patients to cope and prepare for the future.